SUPERVISORS AND SUPERVISEES' PERCEPTION OF INSTRUCTIONAL SUPERVISION: THE CASE OF SELECTED BASIC SCHOOLS IN THE CENTRAL REGION OF GHANA - danquah, Mustapha bin; Baidoo, Usman Yaw; Dankwah, Musah; Acheampong, Richmond (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The study probed supervisors’ and supervisee’s perception of instructional supervision in ten basic schools in the central region of Ghana. Two research questions guided the study. Quantitative paradigm was used to analyze data, while the descriptive survey was employed to analyze closed and opened-ended questions. 100 respondents which comprised 30 supervisors (headteachers and their assistants and head of departments) and 70 supervisees (teachers) from ten basic schools in the Central region of Ghana were selected for the study.  It was found that the majority of the supervisors and teachers have positive perspectives about instructional supervision in basic school. It also came to the fore that effective supervision is a beacon for teachers’ professional development and a potent tool for improved students’ academic development and scholastic achievement. Consequently, it was recommended that supervisors and supervisees should check their attitude towards supervision since it is sine-qua-non to effective school management. Supervisees with a negative view of supervision should rid themselves of such notion and embrace the liberating and productive (positive) notion inherent in supervision to experience the enduring benefits of pedagogy.